MENAKAR URGENSI PENERAPAN KONSEP KAFA’AH DALAM PERNIKAHAN - Supardiyono, Shofwan; Farkhani; Multazam, Umar (Sekolah Tinggi Islam Syariah (STIS) Al-Ittihad Bima, 2025)
This article examines the urgency of implementing the concept of kafa’ah (compatibility) in marriage from an Islamic perspective. The concept encompasses equality in religion, morality, social status, economy, and education, which are believed to contribute to a harmonious household. The research employs a literature review method with a descriptive qualitative approach. The findings indicate that while scholars differ on the specific elements of kafa’ah, most agree that faith and piety are the essential foundations in selecting a life partner. The application of kafa’ah remains relevant in the contemporary era to build a sakinah (peaceful), mawaddah (loving), and rahmah (compassionate) family. Keywords: Kafa’ah, Islamic marriage, family harmony, faith, equality.